2019
DOI: 10.4103/jnrp.jnrp_237_18
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern in Adult Patients with Acute Stroke in South India: A Case-Control Study from a Tertiary Care Center in Hyderabad

Abstract: Background and Objective: Diet plays a crucial role in the occurrence of stroke. But very few studies have so far been conducted with focus on this aspect of acute stroke in India. The objective of the study was to identify the dietary pattern in patients with acute stroke in South India. Materials and Methods: Patients with first-ever acute stroke (ischemic and hemorrhagic) admitted between June 2017 and November 2017 were enrolled and compared with age- and sex-matched controls. Information was collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Another study to know the dietary pattern in adult patients with acute stroke was conducted in South India (Hyderabad). 17 This was a prospective case control study and 150 participants with first ever stroke (Ischemic and haemorrhagic) were compared with 150 age and sex matched healthy control. 17 Dietary habits and patterns of diet were obtained using a food frequency questionnaire with a list of 55 food items and how often it was consumed.…”
Section: Dietary Pattern and Stroke Studies From Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Another study to know the dietary pattern in adult patients with acute stroke was conducted in South India (Hyderabad). 17 This was a prospective case control study and 150 participants with first ever stroke (Ischemic and haemorrhagic) were compared with 150 age and sex matched healthy control. 17 Dietary habits and patterns of diet were obtained using a food frequency questionnaire with a list of 55 food items and how often it was consumed.…”
Section: Dietary Pattern and Stroke Studies From Indiamentioning
confidence: 99%
“…17 This was a prospective case control study and 150 participants with first ever stroke (Ischemic and haemorrhagic) were compared with 150 age and sex matched healthy control. 17 Dietary habits and patterns of diet were obtained using a food frequency questionnaire with a list of 55 food items and how often it was consumed. Mean age of stroke patients in this study was 52.4±12.6 years.…”
Section: Dietary Pattern and Stroke Studies From Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…7 Some studies have established DPs related to stroke and CVD risk. [8][9][10][11] However, this information is yet to be established among indigenous African populations. It might be suitable to apply DP analysis to discern dominant dietary factor(s) for stroke events among indigenous Africans.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In the journal, Durga and Manorenj found that stroke patients from Hyderabad district had lower intake of green leafy vegetables, roots, tubers, fruits, prawns, crab and water, and higher intake of red meat, organ meat, fried snacks, and fruit juices. [13] Such studies are a starting point to make local and national dietary guidelines.…”
mentioning
confidence: 99%